2011
DOI: 10.1111/j.1468-2478.2010.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Modernization vs. Dependency Revisited: Effects of Foreign Direct Investment on Food Security in Less Developed Countries1

Abstract: Food security is of great urgency in the developing world. Many countries have sought to attract foreign capital to promote development and reduce hunger. But how do foreign direct investment (FDI) inflows affect food security? Extant research based on dependency and modernization arguments or the globalization debate offers contradictory theoretical predictions and produces conflicting evidence. We resolve the puzzle by disaggregating FDI. Foreign investments in distinct economic sectors have disparate attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 91 publications
1
53
0
Order By: Relevance
“…17,18 Investment in agricultural land is now high. In 2011, the High Level Panel of Experts on Food Security and Nutrition reported that international investors had leased or purchased an estimated 50 to 80 million hectares of land in middleand low-income countries, about two thirds of them in sub-Saharan Africa.…”
Section: Foreign Direct Investment and Nutrition Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Investment in agricultural land is now high. In 2011, the High Level Panel of Experts on Food Security and Nutrition reported that international investors had leased or purchased an estimated 50 to 80 million hectares of land in middleand low-income countries, about two thirds of them in sub-Saharan Africa.…”
Section: Foreign Direct Investment and Nutrition Regulationmentioning
confidence: 99%
“…17 Governments promote investment in agricultural production through various types of subsidies. As is true of other incentives to attract FDI, such subsidies and other measures to promote food security can lower the cost of producing the products that are of greatest concern in a public health nutrition context.…”
Section: Investor Protection and Public Health Nutrition Policymentioning
confidence: 99%
“…Foreign investment is mainly concentrated in export industries and has weak links with the internal market, which also has a negative impact on domestic production. In the short term, FDI can create economic growth, but the long-term effects of the penetration of foreign capital are negative [12].…”
Section: The Impact Of Investment On Food Security: the Theoretical Bmentioning
confidence: 99%
“…For hunger to reduce, it is important that adequate infrastructure, relevant policies, and implementation of policies that boost rural and local food production be put in place. The activities of agricultural FDI has shown that the mechanisms through which PFDI operates in many oil rich developing countries like Nigeria, often exacerbates food security as the government action is sometimes misplaced as they focus on FDI into the oil sector to the detriment of the agricultural sector (Mihalache-O'keef & Li, 2011).…”
Section: Primary Foreign Direct Investment (Pfdi)mentioning
confidence: 99%
“…Such a mechanism, in the view of Mihalache-O'keef & Li (2011), is a recommended pathway that alleviates hunger.…”
Section: Primary Foreign Direct Investment (Pfdi)mentioning
confidence: 99%